Nanostructure oxygen carrier used in chemical looping combustion process-A review - Badadare, Mansing M.; Adbale, Naina M.; Khomane, Ramdas B.; Kale, Ganesh R. (Advanced Science Letters, 2016)
Chemical looping combustion (CLC) is an emerging technology with inherent separation of CO2 from combustion of fuels. In this technique contact of air and fuel for combustion is restricted by providing oxygen through oxygen carrier (DC). The functional efficiency of CLC process mainly depends on the ability of oxygen carrier and it's reactivity, which undergoes repeated oxidation and reduction cycles. Nanostructure metal oxides have shown great potential application in the field of chemical looping combustion due to their high surface to volume ratio and enhanced structural properties. Synthesis technique of nanostructure metal oxides, their role as oxygen carrier, their reactivity with fuels along with their structural stability are reviewed herein. The contribution of various operating conditions on nanostructure oxygen carrier are considered in this review. These operating conditions and synthesis routes are summarized and classified according to metal oxides.
Keywords: Chemical looping combustion; CO2 Emission; Metal Oxide; Nanostructure; Oxygen Carrier